Paul's letter to the Romans and Roman imperialism: an ideological analysis of the Exordium (Romans 1:1-17) - Rock, Ian E. (James Clarke & Co, 2017)
A new reading of First Romans as an anti-imperial missive, revealing the complex interplay between theology and ideology